AB207. SOH26AB_0261. Evaluating initial management of acute pancreatitis: a 5-month clinical audit at a Portiuncula University Hospital - Minogue, Ashley; O’Dowling, Aidan; Garvin, Joesph (Mesentery and Peritoneum, 2026)
Acute pancreatitis (AP) is often a mild self-limiting illness, but in severe cases, it is associated with high mortality rates. Initial management of AP is a cornerstone of treatment to prevent severe disease progression. This audit aimed to assess the initial management of AP to Portiuncula University Hospital (PUH) as recommended by the 2003 Royal College of Surgeons Ireland guidelines, 2018 UK National Institute for Health and Care Excellence (NICE)guidelines, and 2024 American College of Gastroenterology guidelines. It also aimed to assess the utilization of a new screening and management tool for AP in PUH.